Study of Patients with Diabetic Ketoacidosis Admitted at the Pediatric Emergency Service at Childrens Hospital Dr. Jeser Amarante Faria (Global Journal of Medical Research, 2023)
A retrospective study based on the review of medical records in the Tasy system of patients admitted with diabetic ketoacidosis in the emergency service at Children s Hospital Dr Jeser Amarante Faria Joinville-SC 88 medical records were analyzed corresponding to 71 patients nine patients with more than one hospitalization a majority of females 78 age range from 1 3 to 17 1 years A mean of five days of hospitalization with 21 cases requiring hospitalization in the intensive care unit was noted along with severe diabetic ketoacidosis in 59 consultations Patients who never had a diabetic decompensation were 44 of the consultations Hypoglycemia was the most common complication 24 and no deaths were recorded during the evaluated period Girls with a mean age of 10 years were the main group admitted with diabetic ketoacidosis and this medical emergency is still often the first manifestation of type 1 diabetes mellitus in our midst
Keywords: diabetes mellitus type1 ∙ diabetic ketoacidosis ∙ pediatrics